Eduard Petrů's legacy in the study of medieval literature with regard to Petr of Chelčice's work - Soleiman Pour Hashemi, Michaela (Bohemica Olomucensia, 2019)
The study deals with the contribution of the Olomouc professor Eduard Petrů (1928-2006), especially to the research on the work of Petr of Chelčice and his personality (ten basic studies and two editions in total). First, the author presents substantial publications in which E. Petrů dealt with the topic. She concludes that the most frequently cited item is his List of Chelčický's Works. Furthermore, she summarizes that the legacy of E. Petrů in Chelčický's research is followed in particular by Jaroslav Boubín (1954), who is still the author of six publications connected with Chelčický (2005-2018), in which E. Petrů is also properly cited. In a note, she states that in the line of E. Petrů she translated Chelčický's texts into new Czech (together with Jan Rokyta) in the publication The Time and Work of Petr Chelčický (2013). Finally, she concludes that the research legacy of E. Petrů is alive, also thanks to the university textbooks often used (Lehár et al. 1998; Machala et al. 2015).
Keywords: Eduard Petrů; Petr Chelčický